2009
DOI: 10.21273/hortsci.44.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Primocane-fruiting Blackberries: Potential for Extending Harvest Season and Production Regions

Abstract: Primocane-fruiting blackberries produce fruit on current-season canes (primocanes) and second-season canes (floricanes), if desired. Primocane-fruiting blackberries are likely adapted to a diverse range of climates, particularly because cold hardiness is not an issue when plants are grown for a primocane crop only. The floricane crop of ‘Prime-Jan’® and ‘Prime-Jim’® is from 3 June to 6 July in Arkansas and 30 June to 22 Aug. in Oregon, thus overlapping with other fresh market blackberries. However, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The majority of the culled fruit was considered unmarketable (too soft to ship) and therefore unsuitable for commercial production. Strik and Thompson (2009) report that quality of fruit harvested from the floricane crop of 'Prime-JimÒ' and 'Prime-JanÒ' is lower than that of fruit harvested from other floricane-fruiting cultivars. Although no formal postharvest assessments of the ''NC'' experimental cultivars were conducted, notes from harvest indicate that the majority of the culled fruit was soft and therefore not marketable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the culled fruit was considered unmarketable (too soft to ship) and therefore unsuitable for commercial production. Strik and Thompson (2009) report that quality of fruit harvested from the floricane crop of 'Prime-JimÒ' and 'Prime-JanÒ' is lower than that of fruit harvested from other floricane-fruiting cultivars. Although no formal postharvest assessments of the ''NC'' experimental cultivars were conducted, notes from harvest indicate that the majority of the culled fruit was soft and therefore not marketable.…”
Section: Resultsmentioning
confidence: 99%
“…Season extension techniques are used to advance or delay the fruiting season of many small fruit crops including raspberry (Rubus idaeus) and blackberry (Pritts, 2008;Pritts et al, 1992;Strik and Thompson, 2009;Strik et al, 2008). When rowcovers were applied over the rows of primocanefruiting raspberries in the early spring before primocane emergence, fruit production occurred up to 3 weeks earlier than in rows without rowcovers.…”
mentioning
confidence: 99%
“…Primocane-fruiting blackberries may offer the advantage of extending the harvest into the fall and winter months, particularly in milder climates (average annual minimum temperature -12°C or greater; Strik and Thompson, 2009). Oliveira et al (1996Oliveira et al ( , 1998Oliveira et al ( , 2004 and Jordan and Ince (1986) have shown that harvest of primocane-fruiting raspberry can easily be delayed in production systems that include summer pruning of primocanes, tipping, and tunnel protection.…”
mentioning
confidence: 99%
“…The parameters of TSS, TTA and pH were determined by macerating 10 g of fruit per site to obtain juice. The TSS In view of the situation described above, several alternative crops have been evaluated which, in addition to having lower water and cold winter requirements (Strik and Thompson, 2009;Segantini et al, 2015;Cera-Campos et al, 2019), allow the producer maintain and/or acquire an adequate economic income for their families (Parra-Quezada et al, 2008;El Yaacoubi et al, 2016), with the consequent generation of jobs and economic benefits as part of the implementation of the systems of production (Clark and Finn, 2014;Frias-Moreno et al, 2019). Among these alternatives are the blackberry (Rubus sp.…”
Section: Floweringmentioning
confidence: 99%